Skin Related Problems Among Women of Reproductive Age Suffering from Polycystic Ovarian - Hassan, Anam; Akbar, Rashida; Mustafa, Hira; Ali, Summiya; Zara; Seema (Indus Journal of Bioscience Research, 2025)
Background: Hirsutism, androgenic alopecia, acne, and seborrhea are among the skin abnormalities associated with PCOS that are brought on by hyperandrogenemia. Many women with PCOS also have dark keratosis, which is linked to insulin resistance. Objective: The purpose of this study is to ascertain the frequency of cutaneous symptoms linked to PCOs. Materials and Methods: This cross-sectional study was conducted at the People's University of Medical and Health Sciences for Women, Shaheed Benazirabad, Sindh, from August to December of 2024. One hundred PCO patients between the ages of 15 and 45 years were recruited for the study. Androgenic alopecia was evaluated using Ludwig's classification. A modified Ferriman Gallway (F-G) score was used to determine the severity of hirsutism, Acanthosis nigricans is a long-term skin disorder that affects the neck, major flexures, and acral regions and is characterized by velvety thickening and hyperpigmentation. Patients under the age of 15, those with thyroid, pituitary, hypothalamic, or adrenal disorders, and those on any hormonal, lipid-lowering, or hypoglycemic treatments were not allowed to participate in the trial. Results: The study's age range was 18 to 45 years old, with a mean age of 28.81 ± 4.83 years. PCOS lasted an average of 3.68 ± 1.60 years. According to study, hirsutism, acne, female pattern hair loss, acanthosis nigricans, seborrhea, striae, and acrochordons were found in 75.63%, 65.0%, 34.38%, 30.0%, 24.38%, 11.88%, and 11.25% of PCOS patients, respectively. Conclusion: Dermatological signs are part of the phenotypic profile of PCOS.  In addition to being crucial in the diagnosis of PCOS, they may have long-term psychological and aesthetic effects on the patient's social and quality of life.